NAVIGATING CHALLENGES IN LEARNING SPEAKING SKILLS AMONG ISLAND STUDENTS - Carli Alfian; Rona Elfiza; Erwin Pohan (Universitas Maritim Raja Ali Haji (UMRAH), 2026)
This study examines the challenges encountered by seventh-grade students at SMPN 9 Tanjungpinang, located on Penyengat Island, in learning English speaking skills. The study examines three categories of challenges: linguistic, psychological, and social-socio-cultural. This study employed a mixed method methodology, incorporating speaking assessments and interviews as research instruments. The findings indicate that students encounter difficulties due to limited vocabulary and a lack of sentence organization skills. Anxiety, shyness, and low self-esteem significantly affect their ability to communicate. In addition, the students are having trouble because of social and cultural reasons including not having much exposure to English in their community, the fact that the local language (Bahasa Melayu) is the most common one, and not having relatives or friends who speak English. The report says that island students need more English-speaking practice that is relevant to their lives, inspiring, and participatory, and that teachers, school programs, and family members should all help with this.